Improved erythema and decreased blister formation in dominant dystrophic epidermolysis bullosa following treatment with pulsed dye laser. Issue 6 (5th September 2022) - Garza‐Mayers, Anna Cristina; Su, Katherine A.; Wiss, Karen
Abstract: Dominant dystrophic epidermolysis bullosa (DDEB), an inherited disorder due to type VII collagen mutations, is characterized by blisters and erosions that heal with scarring, atrophy, and milia. There is no established role for laser in the management of patients with DDEB. Pulsed dye laser (PDL) is most often used to target vascular skin lesions. We describe a patient with DDEB with marked improvement in erythema as well as fewer and less symptomatic episodes of blistering following treatment with PDL.